Proses Penegakan Hukum Terhadap Kasus Investasi Bodong PT Dana Oil Konsorsium (PT Dok) Oleh Polda Bali - Dewa Ayu Sri Ratih; I Ketut Sukewati Lanang Putra Perbawa (Jurnal Hukum Mahasiswa, 2026)
This research analyzes law enforcement against corporate illegal investment involving PT Dana Oil Konsorsium (PT DOK) within the Bali Regional Police jurisdiction. Utilizing an empirical legal method with a socio-legal perspective, this study evaluates investigative measures and factors inhibiting the legal process. Findings indicate that despite repressive efforts and inter-institutional coordination, primary obstacles include limited evidence, difficulties in asset tracing, and the vast distribution of victims. However, high legal awareness among victims serves as a significant supporting factor. The author recommends strengthening regulations and law enforcement capacity to address the complexities of corporate crime. This synergy is crucial to ensure legal certainty and public protection